INTERPRETASI MAKNA TEKS LAGU TIKUS-TIKUS KANTOROLEH IWAN FALS - Raja Saleh (Madah: Jurnal Bahasa dan Sastra, 2012)
The object ive of this research is to describe the meaning of song interpretation, titled Tikus-Tikus Kantor by Iwan Fals. The data were collected by listening some of Iwan Falss songs, choosing one of them, and transcripting the song Tikus-Tikus Kantor. The data were analyzed by describing each line of the song by using hermeneutic approach. This research showed that the song is about social critic to the coruption by government official and law enforcement.